Analysis of The Effectiveness of Information Communication Technology and The Service Marketing Mix to Customer Loyalty Indihome - Raihanah Daulay (AIBPM Publisher, 2021)
Customer loyalty is a very important thing for one business. Maintaining it becomes a priority for long-term gain. There are many things every company can do in order to retain its customers. Providing information communication technology that suits the customer's wishes and executing the right service marketing mix strategy can be done to retain customers. The purpose of this research is to find out the influence of information communication technology and the service marketing mix on customer loyalty. The population of this study is Telkomsel customers who use indihome devices for more than two years in Medan. Data collection techniques using online questioners are tested for validity and reliability. Data analysis techniques use multiple liner regression, classical assumption tests and hypothesis tests. The results showed that partially information communication technology has a significant effect on customer loyalty, partially the service marketing mix has a significant effect on customer loyalty and simultaneously information communication technology and service marketing mix has a significant effect on indihome customer loyalty.